COMMUNITY SERVICE: EXPERIENCES AND CHALLENGES OF IMPLEMENTATION IN THE REPUBLIC OF SERBIA IN THE 2015-2020 PERIOD - Milica Kolaković-Bojović; Ana Batrićević (Revija za kriminologiju i krivično pravo)
The dual nature of the community service makes this punishment, on the one hand, an effective mechanism for reducing the overcrowding of penitentiaries, while at the same time enabling effective rehabilitation and reintegration of convicts, through contribution to the local community. Despite the fact that Serbia has been facing the problem of overcrowding of prisons for a long time, and that the punishment of work in the public interest, although in different modalities, has been recognized for decades as one of the key mechanisms for addressing this problem, the pioneer attempts to address this problem have started fifteen years ago. The adequate preconditions to increase a share of the community service in the total number of the imposed criminal sanctions were created by the amendments to the legal framework in 2014. With this in mind, in this paper, the authors present the results of the application of the community service, collected as part of a comprehensive impact assessment research on the application of alternative sanctions and measures in the Republic of Serbia in the 2015-2020 period. The basis for the conclusions presented in this paper are founded on the basis of the data collected by triangulation of quantitative and qualitative research methods and analysed from the perspective of the efficiency, effectiveness and sustainability of the existing system. The paper also defines a set of recommendations for improving the normative framework and its application in practice and assesses their compatibility with the measures envisaged by the Strategy for the Development of the System of Execution of Criminal Sanctions for the 2021-2027 period.